60-Hour Sleep Deprivation Affects Submaximal but Not Maximal Physical Performance - Vaara, Jani P.; Oksanen, Hermanni; Kyröläinen, Heikki; Virmavirta, Mikko; Koski, Harri; Finni, Taija (Frontiers in Physiology, 2018)
ABSTRACT The effect of 60-h sleep deprivation (SD) on physical performance and motor control was studied. Twenty cadets were measured for aerobic performance (VO2) before and immediately after the SD period. Maximal strength and EMG of the knee extensor muscles were measured before and after 60 hours of SD. Balance, reaction times and motor control were assessed every evening and morning during the SD period. Main effects were observed for heart rate (p=0.002, partial eta squared, η: 0.669), VO2 (p=0.004, partial eta squared: 0.621), ventilation (p=0.016, partial eta squared: 0.0.49) and lactate concentration (p=0.022, partial eta squared: 0.501), whereas RER remained unaltered (p=0.213, partial eta squared: 0.166). Pairwise comparisons revealed decreased values at submaximal loads in heart rate, VO2, ventilation (all p<0.05) but not in RER, whereas all of their respective maximal values remained unchanged. Moreover, pairwise comparisons revealed decreased lactate concentration at maximal performance but only at 8-minute time point during submaximal workloads (p<0.05). Pairwise comparisons of maximal strength, EMG and rate of force development revealed no change after SD. Main effects were observed for motor and postural control, as well as for reaction times (all p<0.05), whereas pairwise comparison did not reveal a consistent pattern of change. In conclusion, motor control can mostly be maintained during 60-hour SD, and maximal neuromuscular and aerobic performances are unaffected. However, submaximal cardiorespiratory responses seem to be attenuated after SD.